ESTUDO COMPARATIVO DA POSIÇÃO ÂNTERO POSTERIOR DOS PRIMEIROS MOLARES INFERIORES NO TRATAMENTO ORTODÔNTICO, UTILIZANDO AS TÉCNICAS STRAIGHT-WIRE E EDGEWISE, EM CASOS DE MÁ OCLUSÃO DE CLASSE I DE ANGLE, COM EXTRAÇÃO DE PRIMEIROS PRÉ-MOLARES - Ferreira, Daniella Prado (2005)
This study evaluated the anterior-posterior position of the lower first molars, during the orthodontic treatment, using a lingual arch as an anchorage accessory in the Straight-Wire technique, in comparison to the cases treated by the Edgewise technique, without the use of a lingual arch. Two groups were selected, both presenting with Angle7 Class I malocclusion, treated with the extraction of upper and lower first premolars. The sample consisted of 255 lateral cephalometric x-rays obtained from Brazilian patients. The patients were of both genders, with an average age between 13 years and 6 months and with different standards of facial growth. Based in the analysis and discussion of the results, it was concluded that: 1) from the start of treatment to the end of leveling phase, the lost of anchorage by mesial crown tipping of lower first molar was greater in the cases treated with Straight-Wire technique; 2) from the end of leveling phase to the end of treatment, the lost of anchorage by bodily movement of the lower first molar was greater in the Edgewise technique; 3) from start to end of treatment the total anchorage loss was greater in the patients treated with Edgewise technique; e 4) the anterior-posterior movement of the lower incisors did not shown any statistically significant difference for both techniques, in all phases of treatment.(AU)